Sistem Pakar Diagnosa Penyakit Lambung Menggunakan Metode Certainty Factor - Dwi Ranti; Anita Desiani; Sugandi Yahdin; Syafrina Lamin (Politeknik Negeri Lhokseumawe, 2023)
The digestive system is very important for humans, there are several digestive systems, one of which is the stomach. The main function of the stomach in the digestive system is to store and digest food before it is absorbed by the body's cells as a source of energy. A healthy lifestyle in life is very important, including maintaining a diet, not eating carelessly, and getting enough rest. An unhealthy life will also trigger various diseases, one of which is gastric disease. Early and accurate diagnosis of kidney disease can aid in timely and effective management of the condition. an expert system for diagnosing gastric disease with the CF (Certainty Factor) method to assist people in diagnosing gastric disease along with advice based on perceived treatment symptoms. This study aims to develop an expert system for diagnosing kidney disease using the CF method. The developed system consists of components of data collection, data storage, and data processing, with the CF method used to calculate the diagnosis level of confidence and make decisions based on predetermined rules. The CF (Certainty Factor) method shows a measure of certainty about a fact, it is known that user 1, user 3, user 4, and user 5 have the highest proportion of gerd disease, namely 36.7%, 38.8%, 48.9%, 47.6%. While user 2 has the highest proportion of stomach cancer with 24.8%. So this study only has an accuracy rate of 80%. Diagnosis can be an alternative to early detection of several types of gastric disease.